2015
DOI: 10.1155/2015/294127
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in the Behavioral Symptom Severity of Prader-Willi Syndrome

Abstract: Objectives. This study measured gender differences in Prader-Willi syndrome (PWS) in regard to the severity of behavioral symptoms. Methods. The Food Related Problem Questionnaire (FRPQ), the Aberrant Behavior Checklist Japanese Version, the Childhood Routines Inventory, the Pervasive Developmental Disorders Autism Society Japan Rating Scale, and Japanese ADHD-RS were administered to PWS patients (45 males aged 6 to 58 and 37 females aged 6 to 45). To examine the effects that gender and genotype have on the se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…Girls scored higher than boys for food-related obsessive speech and compulsive behaviors including hiding or hoarding. At least one other study has found that food-related behaviors differ based on both sex and genetic subtype of PWS, with less severe behavior reported in males within the UPD subtype [37]. More research studies focused on potential sex-based differences in behavioral phenotypes of PWS are needed.…”
Section: Discussionmentioning
confidence: 99%
“…Girls scored higher than boys for food-related obsessive speech and compulsive behaviors including hiding or hoarding. At least one other study has found that food-related behaviors differ based on both sex and genetic subtype of PWS, with less severe behavior reported in males within the UPD subtype [37]. More research studies focused on potential sex-based differences in behavioral phenotypes of PWS are needed.…”
Section: Discussionmentioning
confidence: 99%
“…This may have been due to a sampling bias as we had more female than male PWS subjects. However, there is some evidence that rates of behavioral abnormalities in PWS are similar between genders, which may explain the difference in expected ASD gender distribution in PWS compared to the DS or ASD alone group (Gito et al, ; Sinnema et al, ). One study showed similar scores on the Developmental Behavior Checklists for adults between genders in PWS for total and subscale scores but did note higher scores for females on questions regarding irritability and becoming upset over small changes in routine or environment (Jauregi, Laurier, Copet, Tauber, & Thuilleaux, ).…”
Section: Discussionmentioning
confidence: 99%
“…In stark contrast to male Cyfip1 J/mice with the maternal deletion, female Cyfip1 J/mice ( Fig.3F,G) with the paternal Cyfip1 J/deletion showed a markedly enhanced, initial consumption of PF that obfuscated detection of escalation over time (Fig.4H,I). In considering sex differences in PWS, male PWS patients with 15q11-q13 deletions showed greater food-related preoccupation with food, impaired satiety, and other food-related negative behaviors in the absence of differences in OC or other non-food-related behaviors 70 . It is unclear whether sex differences in food-related problems differ depending on Type I versus Type II PWS deletions.…”
Section: Effect Of Cyfip1 Deletion On Pf Intake Depends On Genetic Bamentioning
confidence: 99%